Heart team approach in treatment of mitral regurgitation: patient selection and outcome. Issue 2 (19th July 2020) - Külling, Mischa; Corti, Roberto; Noll, Georg; Küest, Silke; Hürlimann, David; Wyss, Christophe; Reho, Ivano; Tanner, Felix C; Külling, Jeremy; Meinshausen, Nicolai; Gaemperli, Oliver; Wenaweser, Peter; et al.
Abstract : Objective: A multidisciplinary heart valve team is recommended for the evaluation of treatment in patients with valvular heart disease, but evidence supporting this concept is lacking. In patients with severe mitral regurgitation, we thought to analyse the patient selection process by the heart team for different treatment options and the outcome after treatment. Methods: In this single-centre cohort study, all patients treated for mitral regurgitation between July 2013 and September 2018 were included. Primary end points during follow-up were all-cause mortality and a combined end point, consisting of all-cause mortality, cardiovascular rehospitalisation and mitral valve reintervention. Results: 179 patients (44.8%) were treated using Mitraclip, 185 (46.2%) by surgical repair and 36 (9.0%) by surgical replacement. The mortality risk according to EuroScore II differed significantly between treatment groups (6.6%±5.6%, 1.7%±1.5% and 3.6%±2.7% for Mitraclip, surgical repair and replacement, respectively, p<0.001). In-hospital mortality for the 3 groups were 3.4%, 1.6% and 8.3%, respectively (p=0.091). Overall, surgical repair patients had higher 4-year survival (HR 0.40 (95% CI 0.26 to 0.63), p<0.001) and fewer combined end points (HR 0.51 (95% CI 0.32 to 0.80), p<0.001) compared with surgical replacement and Mitraclip patients. However, patients undergoing Mitraclip for isolated, primary mitral regurgitation achieved very good long-term survival. Conclusion: The multidisciplinary heart team assigned only low-risk patients with favourable anatomy to surgical repair, while high-risk patients underwent Mitraclip or surgical replacement. This strategy was associated with lower than expected in-hospital mortality for Mitraclip patients and high 4-year survival rates for patients undergoing surgical or percutaneous repair of isolated primary mitral regurgitation.